Guru Profesional dan Tantangan Dunia Pendidikan - Jailani, Muhammad Syahran (Institut Agama Islam Negeri Imam Bonjol Padang, 2014)
This article deals with professional teachers and challenges they face in the future. The performance of professional teachers demands hardwork to reconstruct their task and responsibility as educators. Nowadays, they bear burn critiques as researches posted them – Indonesian teachers are now in the critical situation. In the implementation of certification project, for example, the certified teachers performances were unlikely to match with students’ success achievement. Research also confined that there were only 21.07 percents of State Elementary school teachers, twenty-eight point ninety-four percents of Private Elementary school teachers, fifty-four point twelve percents of State Junior High school teachers, and sixty point ninety-nine percents of Private Junior High school teachers who deserved to teach. While there were only sixty-five point twenty-nine percents of State Senior High school teachers and sixty-four point seventy-three Private Senior High scholl teachers who deserved to teach.Copyright © 2014 by Al-Ta'lim All right reservedDOI: 10.15548/jt.v21i1.66